Novel PITX2 Mutations including a Mutation Causing an Unusual Ophthalmic Phenotype of Axenfeld-Rieger Syndrome - Liqin Huang; Yong Meng; Xiangming Guo (Journal of Ophthalmology)
Purpose. The aims of this study were to examine novel mutations in PITX2 and FOXC1 in Chinese patients with anterior segment dysgenesis (ASD) and to compare the clinical presentations of these mutations with previously reported associated phenotypes. Methods. Twenty-six unrelated patients with different forms of ASD were enrolled from our paediatric and genetic eye clinic. The ocular manifestations of both eyes of each patient were recorded. Genomic DNA was prepared from venous leukocytes. All coding exons of PITX2 and FOXC1 were amplified by polymerase chain reaction (PCR) from genomic DNA and subjected to direct DNA sequencing. Analysis of mutations in control subjects was performed by heteroduplex single-strand conformation polymorphism (SSCP) analysis. Results. Sequence analysis of the PITX2 gene revealed four mutations, including c.475_476delCT (P.L159VfsX39), c.64C > T (P.Q22X), c.296delG (P.R99PfsX56), and c.206G > A (P.R69H). The first three mutations were found to be novel. The c.475_476delCT (P.L159VfsX39) mutation, located at the 3′ end of the PITX2-coding region, was identified in a Chinese Axenfeld-Rieger syndrome (ARS) patient who presented with an unusual severe phenotype of bilateral aniridia. The clinical characteristics, including the severity and manifestations of the patient’s phenotype, were compared with reported PITX2-associated aniridia phenotypes of ARS in the literature. Conclusions. These results expand the mutation spectrum of the PITX2 gene in patients with ARS. The PITX2 gene may be responsible for a significant portion of ARS with additional systemic defects in the Chinese population. This is the first reported case of a mutation at the 3′ end of the PITX2-coding region extending the phenotypic consequences to bilateral aniridia. The traits of ARS could display tremendous variability in severity and manifestations due to the dominant-negative effect of PITX2. Our results further emphasize the importance of careful clinical and genetic analysis in determining mutation-disease associations and may lead to a better understanding of the role of PITX2 in ocular development.